Does a half-day course about palliative care matter? A quantitative and qualitative evaluation among health care practitioners - Friedrichsen, Maria; Heedman, Per-Anders; Åstradsson, Eva; Jakobsson, Maria; Milberg, Anna (Journal of palliative medicine, 2013)
To date there has been a paucity of research examining whether a course in palliative care influences the clinical work. Therefore a half-day course was started for different professionals. The aims of this study were to quantitatively and qualitatively explore professionals' experience of the usefulness and importance of such a course. An evaluation study was used with two measurement points in the quantitative part; qualitative focus group interviews were conducted three times. Data was collected in Sweden through structured and open-ended questions (n=355) and in focus group discussions (n=40). The majority of participants were allied professionals (86%). Course evaluation immediately after the intervention showed high scores. At three months, 78% of the 86 participants who had cared for a dying patient since the course claimed that the course had been useful in their work. In addition, there were improvements regarding symptom management (37%), support to family members (36%), more frequent break point conversations (31%), and improved cooperation in the teams (26%). The qualitative analysis showed that the course made participants start to compare their own working experiences with the new knowledge. When returning to work, the participants feel strengthened by the the newly acquired knowledge, but the will to improve the care also led to frustration, as some of the participants described that they wanted to change routines in the care of the dying, but felt hindered. The course was appreciated and useful in the professionals' work, but it also created problems.